Eksplorasi Etnomatematika Pada Kue Jalo Khas Kampar - Satifa, Oriza; Misliana, Misliana; Habibi, Mhmd (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
Jalo cake is a traditional cake found in several regions in Indonesia, including the Kampar area. This research aims to explain the relationship between the typical Kampar jalo cake and mathematics, especially in the cultural context of the Kampar community. The methods and approaches used are exploratory and ethnographic. Data was collected through literature study, observation, interviews and documentation. Researchers rely on field observations and interviews in collecting data. The uniqueness of this research is that the Kampar community and students are not yet aware that jalo cake is related to mathematics learning. The connection between mathematics and jalo cakes includes material about triangular shapes and cylinder shapes, which are studied in the 5th grade of elementary school.